Why Tin‐Doping Enhances the Efficiency of Hematite Photoanodes for Water Splitting—The Full Picture. (19th September 2018) - Hufnagel, Alexander G.; Hajiyani, Hamidreza; Zhang, Siyuan; Li, Tong; Kasian, Olga; Gault, Baptiste; Breitbach, Benjamin; Bein, Thomas; Fattakhova‐Rohlfing, Dina; Scheu, Christina; Pentcheva, Rossitza
Abstract: The beneficial effects of Sn(IV) as a dopant in ultrathin hematite (α‐Fe2 O3 ) photoanodes for water oxidation are examined. Different Sn concentration profiles are prepared by alternating atomic layer deposition of Fe2 O3 and SnO x . Combined data from spectrophotometry and intensity‐modulated photocurrent spectroscopy yields the individual process efficiencies for light harvesting, charge separation, and charge transfer. The best performing photoanodes are Sn‐doped both on the surface and in the subsurface region and benefit from enhanced charge separation and transfer. Sn‐doping throughout the bulk of the hematite photoanode causes segregation at the grain boundaries and hence a lower overall efficiency. Fe2 O3 (0001) and terminations, shown to be dominant by microstructural analysis, are investigated by density functional theory (DFT) calculations. The energetics of surface intermediates during the oxygen evolution reaction (OER) reveal that while Sn‐doping decreases the overpotential on the (0001) surface, the Fe2 O3 orientation shows one of the lowest overpotentials reported for hematite so far. Electronic structure calculations demonstrate that Sn‐doping on the surface also enhances the charge transfer efficiency by elimination of surface hole trap states (passivation) and that subsurface Sn‐doping introduces a gradient of the band edges that reinforces the band bending at the semiconductor/electrolyte interface and thus boosts charge separation. Abstract : Ultrathin hematite films with surface and subsurface tin‐doping show greatly enhanced charge separation and charge transfer in photoelectrochemical water oxidation.